How pervasive is corporate fraud? - Alexander Dyck; Adair Morse; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
We provide a lower-bound estimate of the undetected share of corporate fraud. To identify the hidden part of the "iceberg," we exploit Arthur Andersen's demise, which triggered added scrutiny on Arthur Andersen's former clients and thereby increased the detection likelihood of preexisting frauds. Our evidence suggests that in normal times only one-third of corporate frauds are detected. We estimate that on average 10% of large publicly traded firms are committing securities fraud every year, with a 95% confidence interval of 7%-14%. Combining fraud pervasiveness with existing estimates of the costs of detected and undetected fraud, we estimate that corporate fraud destroys 1.6% of equity value each year, equal to 830 billion in 2021.
Keywords: G30; G34; K22; M40; 330; Corporate governance; Corporate fraud; Detection likelihood; Cost-beneft analysis; Securities regulation; Arthur Andersen